Trastuzumab deruxtecan in HER2-positive advanced breast cancer with or without brain metastases: a phase 3b/4 trial - Harbeck, Nadia; Ciruelos, Eva; Jerusalem, Guy; Müller, Volkmar; Niikura, Naoki; Viale, Giuseppe; Bartsch, Rupert; Kurzeder, Christian; Higgins, Michaela J.; Connolly, Roisin M.; Baron-Hay, Sally; Gión, María; et al. (Nature medicine, 2024)
Trastuzumab deruxtecan (T-DXd) intracranial activity has been observed in small or retrospective patient cohorts with human epidermal growth factor receptor 2-positive (HER2+) advanced/metastatic breast cancer (mBC) and stable or active (untreated/previously treated and progressing) brain metastases (BMs). The phase 3b/4 DESTINY-Breast12 study investigated T-DXd in patients with HER2+ mBC and is, to our knowledge, the largest prospective study of T-DXd in patients with BMs in this setting. Patients (stable/active BMs (n = 263) and no BMs (n = 241)) treated with one or more prior anti-HER2-based regimens received T-DXd (5.4 mg per kg). Primary endpoints were progression-free survival (PFS; BMs cohort) and objective response rate (ORR) per Response Evaluation Criteria in Solid Tumors version 1.1 (non-BMs cohort). Additional endpoints included central nervous system (CNS) PFS, ORR, time to second progression, CNS ORR (BMs cohort), incidence of new symptomatic CNS metastases (non-BMs cohort), time to progression, duration of response, overall survival and safety (both cohorts). No formal hypothesis testing was conducted for this single-arm, open-label study. In the BMs cohort, 12-month PFS was 61.6% (95% confidence interval (CI): 54.9-67.6), and 12-month CNS PFS was 58.9% (95% CI: 51.9-65.3). In the non-BMs cohort, ORR was 62.7% (95% CI: 56.5-68.8). Grade 3 or higher adverse events occurred in 51% (BMs cohort) and 49% (non-BMs cohort) of patients. Investigator-reported interstitial lung disease/pneumonitis occurred in 16% (grade ≥3: 3%) of patients with BMs and 13% (grade ≥3: 1%) of patients without BMs. These data show substantial and durable overall and intracranial activity for T-DXd, supporting its use in previously treated patients with HER2+ mBC irrespective of stable/active baseline BMs. ClinicalTrials.gov identifier: NCT04739761.
Online veröffentlicht: 13. September 2024
Mitglieder der DESTINY-Breast12 study group: Sally Baron-Hay, Belinda Yeo, Nicole McCarthy, Amelia McCartney, Timothy Clay, Nicholas Murray, Andrea Gombos, Hans Wildiers, Joëlle Collignon, Eveline De Cuypere, Katarzyna Jerzak, Stephen Chia, Maja Maraldo, Jeanette Rønlev, Eva Brix, Minna Tanner, Johanna Mattson, Riikka Huovinen4, Pauline Wimberger, Nadia Harbeck, Volkmar Müller, Mattea Reinisch, Hans Tesch, Michael Untch, Peter Fasching,Tjoung-Won Park-Simon, Joke Tio, Michael Braun, Eva Maria Grischke, Frederik Marmé [... und viele weitere]
Gesehen am 10.04.2025